2014
DOI: 10.2119/molmed.2014.00027
|View full text |Cite
|
Sign up to set email alerts
|

Protease Activated Receptor-1 Deficiency Diminishes Bleomycin-Induced Skin Fibrosis

Abstract: Accumulating evidence shows that protease-activated receptor-1 (PAR-1) plays an important role in the development of fibrosis, including lung fibrosis. However, whether PAR-1 also plays a role in the development of skin fibrosis remains elusive. The aim of this study was to determine the role of PAR-1 in the development of skin fibrosis. To explore possible mechanisms by which PAR-1 could play a role, human dermal fibroblasts and keratinocytes were stimulated with specific PAR-1 agonists or antagonists. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Tryptase, thrombin, PAR-1 signaling, and PAR-2 signaling have been implicated in the development of fibrosis through their effects on fibroblasts (25, 31, 32, 37, 40, 75–78). Both PAR-1 and −2 have been implicated in liver fibrosis in mice (79, 80), and both PAR-1 knockout mice and PAR-2 knockout mice are less susceptible to both induced heart disease and inflammation (8183).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptase, thrombin, PAR-1 signaling, and PAR-2 signaling have been implicated in the development of fibrosis through their effects on fibroblasts (25, 31, 32, 37, 40, 75–78). Both PAR-1 and −2 have been implicated in liver fibrosis in mice (79, 80), and both PAR-1 knockout mice and PAR-2 knockout mice are less susceptible to both induced heart disease and inflammation (8183).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the fibrocyte potentiation caused by proteases relies on a suitable protein additive, not solely albumin. Albumin is increased in fibrotic lesions (25) and healing wounds (102), and is decreased in chronic, non-healing wounds (103105), implying that albumin’s presence may mediate the protease signaling that, by activating fibrocyte differentiation, may initiate key aspects of wound healing and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent transmembrane signalling leads, amongst others, to EMT of alveolar epithelial cells and retinal pigment epithelial cells . Moreover, PAR‐1‐dependent signalling drives fibroblast proliferation and extracellular matrix production in vitro, whereas PAR‐1 deficiency limits liver, lung and skin fibrosis in experimental animal models . In the kidney, PAR‐1 is expressed by endothelial cells, podocytes, mesangial cells, and tubular epithelial cells and we recently showed that PAR‐1 potentiates diabetic nephropathy by inducing mesangial cell proliferation and extracellular matrix production …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Moreover, PAR-1-dependent signalling drives fibroblast proliferation and extracellular matrix production in vitro, whereas PAR-1 deficiency limits liver, lung and skin fibrosis in experimental animal models. [12][13][14][15] In the kidney, PAR-1 is expressed by endothelial cells, podocytes, mesangial cells, and tubular epithelial cells 16 and we recently showed that PAR-1 potentiates diabetic nephropathy by inducing mesangial cell proliferation and extracellular matrix production. 17 Based on the key role of PAR-1 in fibroproliferative disease, it is thus tempting to speculate that PAR-1 may be a key factor driving the pathogenesis of renal fibrosis.…”
mentioning
confidence: 99%